Hubungan Pengetahuan Ibu Hamil Dengan Kejadian Keputihan di Wilayah Kerja Puskesmas Kuta Baro, Aceh Besar - Rahmawati Rahmawati; Oktalia Sabrida; Nurlaila Ibrahim (PT. Intelek Cendikiawan Nusantara, 2026)
Vaginal discharge is one of the common reproductive health problems experienced by pregnant women. According to the World Health Organization (WHO), approximately 31.6% of vaginal discharge cases are caused by Candida albicans infection. In Indonesia, about 75% of women have experienced vaginal discharge at least once in their lifetime, and nearly 45% experience recurrent episodes annually. Lack of knowledge regarding reproductive hygiene may increase the risk of vaginal discharge among pregnant women. This study aimed to determine the relationship between pregnant women's knowledge and the incidence of vaginal discharge in the working area of the Kuta Baro Community Health Center, Aceh Besar. This research used an analytical observational design with a cross-sectional approach. The population consisted of 293 pregnant women who attended antenatal care services. A total of 75 respondents were selected using purposive sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square statistical test with a significance level of 0.01. The results showed that 47 respondents (62.7%) had poor knowledge regarding vaginal hygiene, while 53 respondents (71.6%) experienced vaginal discharge. Statistical analysis indicated a significant relationship between pregnant women's knowledge and the incidence of vaginal discharge (p = 0.000; p < 0.01). In conclusion, pregnant women's knowledge is significantly associated with the occurrence of vaginal discharge. Improving health education regarding reproductive hygiene is necessary to reduce the incidence of vaginal discharge during pregnancy.